Physicochemical Analytical Studies on Yttrium‐Doped Triglycine Sulfate Single Crystals. Issue 4 (10th January 2023) - Rafi Ahamed, S.; Suppuraj, P.; Balakrishnan, C.; Kalpana, S.
Abstract: Single crystals of pure triglycine sulfate (TGS) and yttrium‐acetate (0.5 mol%)‐doped triglycine sulfate (YTGS) crystals are synthesized and the crystals are grown from aqueous solution by slow evaporation solution growth method. The grown crystals are subjected to single crystal and powder X‐ray diffraction studies to identify the morphology and structure. Both the grown crystals are packed in a monoclinic crystal system and the lattice parameters of YTGS crystal are a = 9.138 Å, b = 12.72 Å, and c = 5.728 Å, whereas the doped TGS are, a = 9.134 Å, b = 12.61 Å, and c = 5.723 Å. The lattice parameters are slightly distorted due to the incorporation of yttrium ion into the lattice sites of the TGS crystal. The thermal stability of the grown crystals is investigated by differential thermal analysis (DTA) and thermogravimetric studies. DTA curve shows a lower decomposition temperature for YTGS crystal than for pure TGS crystal. The functional groups of the grown crystals are identified by Fourier transform infrared spectral studies. The surface morphology of the crystals is examined by scanning electron microscopy. Dielectric studies are carried out to identify the phase transition temperature and to find the dielectric constant of the YTGS crystals. Abstract : Here, good quality pure and yttrium‐doped triglycine sulfate (TGS) single crystals are harvested using the slow evaporation solution growth method. The scanning electron microscopy analysis reveals that the rod shape and lenticular shape domains are observed in pure and doped TGS crystals, respectively. The low dielectric constants suggest that doped TGS crystals can be a potential material for IR detectors.